N6‐isopentenyladenosine improves nuclear shape in fibroblasts from humans with progeroid syndromes by inhibiting the farnesylation of prelamin A. (18th November 2013) - Bifulco, Maurizio; D'Alessandro, Alba; Paladino, Simona; Malfitano, Anna M.; Notarnicola, Maria; Caruso, Maria G.; Laezza, Chiara
<x xml:space="preserve">Abstract</x> Hutchinson–Gilford progeria syndrome is caused by mutations in the lamin A/C gene that lead to expression of a truncated, permanently farnesylated prelamin A variant called progerin. The accumulation of progerin at the nuclear envelope causes mis‐shapen nuclei and results in progeroid syndromes. Previous studies in cells from individuals with Hutchinson–Gilford progeria syndrome have shown that blocking of farnesylation of prelamin A ameliorates the nuclear shape abnormalities. Here we observed that an inhibitor of farnesyl diphosphate synthase, N6‐isopentenyladenosine, impeded the farnesylation of prelamin A, causing a decrease in the frequency of nuclear shape abnormalities and redistribution of prelamin A away from the inner nuclear envelope. A combination of lovastatin and N6‐isopentenyladenosine significantly improved nuclear shape in fibroblast cell lines from atypical progeria patients. These findings establish a paradigm for ameliorating the most obvious cellular pathology in lamin‐related progeroid syndromes, and suggest a potential strategy for treating children with Hutchinson–Gilford progeria syndrome.